2018
DOI: 10.1111/jerd.12426
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of intraoral photographic orthodontic records

Abstract: Objective The aims of this study were (1) to investigate how relevant intraoral photographs are to contemporary orthodontic diagnosis and (2) to assess orthodontists' ability to accurately diagnose angle classification and dental midlines using standardized intraoral photographs. Methods Study participants were orthodontists who completed a survey regarding photography protocols and their use of intraoral photographs for diagnosis. Each participant was randomized to complete 1 visual diagnostic task regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
1
3
0
4
Order By: Relevance
“…Our results support previous studies, which reported that two‐dimensional digital images are an alternative to orthodontic casts for assessing orthodontic treatment needs by the Index of Orthodontic Treatment Need [22]. However, another study reported that intrasoral photos alone might not be adequate for judging occlusal relationships such as angle classification and esthetic parameters like midlines [23].…”
Section: Discussionsupporting
confidence: 79%
“…Our results support previous studies, which reported that two‐dimensional digital images are an alternative to orthodontic casts for assessing orthodontic treatment needs by the Index of Orthodontic Treatment Need [22]. However, another study reported that intrasoral photos alone might not be adequate for judging occlusal relationships such as angle classification and esthetic parameters like midlines [23].…”
Section: Discussionsupporting
confidence: 79%
“…When color matching has to be evaluated, visual examination is the method of choice. In addition, intraoral photographs can be used but are also difficult to standardize during follow-up examinations [105,106]. In contrast, commercially available color measuring instruments, e.g., reflectance spectrophotometers and colorimeters, have gained acceptance due to their satisfactory accuracy, reliability, and time-efficient use [86,[107][108][109].…”
Section: Colour Match (Category A3)mentioning
confidence: 99%
“…Evidence showed that the possibility of an inaccurate diagnosis of Angle's classification increases seven times when the angle bias is 30 degrees. [20] As the camera perspective changed and ideal photographic conditions were not possible, photographs failed to simulate clinical situations; therefore, the accuracy of Angle's classification diagnosis decreased. However, as the deviation of perspective from the perpendicular degree increased, the apparent lateral distance amplified, and a correct evaluation of the dental arch's space relationship would be more straightforward.…”
Section: Discussionmentioning
confidence: 99%